Occluded superior vena cava and failed epicardial pacing: An unorthodox solution - Nath, Ranjit K; Rajvanshi, Satyam (Journal of Cardiology and Cardiovascular Medicine, 2020)
Permanent pacemaker implantation is conventionally done via upper limb veins. But in 1% - 6% cases, usual sub clavicular approach is either not possible or contraindicated due to complete occlusion of superior vena cava (SVC) or bilateral subclavian vein and/or bilateral implant site infection or thin skin [1]. Alternative approaches are warranted, including leadless pacemaker or complex lead extraction techniques, before considering surgical epicardial lead placement as a last resort because it has own hazards. We report a patient with complete heart block, total SVC obstruction, and a previously implanted malfunctioning epicardial lead presenting with pacemaker end of life. In view of exhaustion of the surgical option and in a resource constrained situation for lead extraction or leadless pacemaker, transiliac endocardial pacemaker implantation was done and a repeat surgery was averted. Learning objective: Complete venous occlusion is not very often encountered after pacemaker/ICD implantation. Apart from the risk of general anesthesia and invasive surgery, epicardial leads increase battery drain, and have a shorter operating life compared to an endocardial lead. The sparingly utilized iliac venous approach for permanent pacemaker implantation is a valuable, safe and minimally invasive alternative, when the conventional percutaneous access is unavailable, and surgery is undesirable or not possible.